Molecular microbial ecology - Osborn, A. Mark; Smith, Cindy J., (Cindy Jane), 1977-; Milling, Annett; Gomes, Newton Carlos Marcial; Oros Sichler, Miruna; Götz, Monika; Smalla, Kornelia (BIOS advanced methods., 2005)
"Molecular Microbial Ecology gives a comprehensive guide to the recent revolution in the study of microorganisms in the environment. Details are given on molecular methods for isolating some of the previously uncultured and numerically dominant microbial groups. PCR-based approaches to studying prokaryotic systematics are described, including ribosomal RNA analysis and stable isotope probing. Later chapters cover DNA hybridization techniques (including fluorescent in situ hybridization), as well as genomic and metagenomic approaches to microbial ecology. Gathering together some of the world's leading experts, this book provides an invaluable introduction to the modern theory and molecular methods used in studying microbial ecology."